Analisa Faktor Perilaku Berkendara Pada Siswa SMA Muhammadiyah 3 Jember - Septianto Hary Prassetyo; Gymnastiar Tira Wicaksana; Fatach Toriqo Abimanyu (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
Traffic accidents can occur due to the non-compliance of motorized vehicle users in traffic. Traffic accidents can have harmful effects both for the motorbike users themselves and for other people. The impacts are not only limited to material things but can also be physical damage and can resulting in fatal permanent disability. There have been many incidents in traffic accidents, of which not the least of which have resulted in lives being lost. In this day and age due to the rapid development of technology, especially in transportation vehicles, it has caused various kinds of problems. it rarely comes from school children, many school children now use motorized vehicles to school. The aims of this research are: 1) To find out what factors cause students to bring motorbikes to school, 2) To understand students' knowledge about rules in traffic, 3) Knowing the attitude of students in riding motorbikes on the highway